Гармонізація ринку освітніх послуг закладів позашкільної музичної освіти країн ЄС та України - Літвяк, А.В. (Економічний вісник Донбасу, 2024)
У сучасних умовах глобалізації та інтеграційних процесів між Україною та Європейським Союзом (ЄС) особливо актуальною стає тема гармонізації ринку освітніх послуг, зокрема у сфері позашкільної музичної освіти. Гармонізація освітніх стандартів та підходів між країнами ЄС та Україною дозволяє створити єдиний освітній простір, який забезпечує високий рівень підготовки фахівців, конкурентоспроможних як на національному, так і на міжнародному ринках праці.
Стаття присвячена аналізу ключових аспектів гармонізації ринку освітніх послуг у сфері музичної освіти, що включає в себе розгляд нормативно-правової бази, аналіз методів та інструментів, що використовуються для гармонізації, а також оцінку впливу цих процесів на розвиток позашкільної музичної освіти в Україні. Значна увага приділяється дослідженню досвіду країн ЄС у впровадженні єдиних стандартів освіти, зокрема в галузі музичної освіти, та його можливому застосуванню в українському контексті.
Стаття також аналізує існуючі проблеми та виклики, що стоять на шляху гармонізації, серед яких можна виділити необхідність адаптації національного законодавства, підвищення рівня професійної підготовки викладачів, а також забезпечення фінансової та інституційної підтримки цього процесу з боку держави та міжнародних організацій. Крім того, обговорюються перспективи розвитку ринку освітніх послуг в Україні в умовах інтеграції до європейського освітнього простору.
У результаті дослідження, виявлено, що гармонізація ринку освітніх послуг у сфері позашкільної музичної освіти є необхідним кроком для забезпечення конкурентоспроможності української освітньої системи, її інтеграції в європейський простір та підвищення якості музичної освіти. Це також створює передумови для розвитку культурного обміну та збереження національних музичних традицій, що сприяє формуванню унікального культурного ландшафту Європи.
Загалом, гармонізація освітніх послуг у сфері музичної освіти має стати основою для розвитку стійкої та якісної освітньої системи, яка відповідатиме потребам сучасного суспільства та викликам глобального ринку праці. In the current conditions of globalization and integration processes between Ukraine and the European Union (EU), the topic of harmonization of the educational services market, in particular in the field of extracurricular music education, becomes especially relevant. Harmonization of educational standards and approaches between the EU countries and Ukraine allows creating a single educational space that provides a high level of specialists’ training competitive both at the national and international labor markets.
The article is devoted to the analysis of harmonization key aspects of the educational services’ market in the field of music education, which includes consideration of the legal framework, analysis of methods and tools used for harmonization, as well as assessment of the these processes’ impact on the development of extracurricular music education in Ukraine. Considerable attention is paid to the study of the experience of the EU countries in the uniform standards’ implementation of education, in particular in the field of music education, and its possible application in the Ukrainian context.
The article also analyzes the existing problems and challenges that stand in the way of harmonization, among which are the need to adapt national legislation, improve the level of teachers’ professional training, as well as provide financial and institutional support for this process from the state and international organizations. In addition, the prospects for the educational services market development in Ukraine in terms of integration into the European educational space are discussed.
As the result of the study, it was found that the harmonization of the educational services’ market in the field of extracurricular music education is a necessary step to ensure the competitiveness of the Ukrainian educational system, its integration into the European space and improving the music education quality. It also creates preconditions for the cultural exchange development and national musical traditions preservation, which contributes to the formation of a unique cultural landscape in Europe.
In general, the educational services harmonization in the field of music education should become the basis for the development of a sustainable and high-quality educational system that will meet the needs of modern society and the challenges of the global labor market.